Asymptotic Field Near the Tip of a Debonded Anticrack in an Anisotropic Elastic Material. Issue 1 (20th February 2020) - Wang, Xu; Schiavone, Peter
Summary: We use the sextic Stroh formalism to study the asymptotic elastic field near the tip of a debonded anticrack in a generally anisotropic elastic material under generalised plane strain deformations. The stresses near the tip of the debonded anticrack exhibit the oscillatory singularities r^-3/4± iε and r^-1/4± iε (where ε is the oscillatory index) as well as the real power-type singularities r^-3/4 and r^-1/4 . Two complex-valued stress intensity factors and two real-valued stress intensity factors are introduced to respectively scale the two oscillatory and two real power-type singularities. The corresponding three-dimensional analytic vector function is derived explicitly, and the material force on the debonded anticrack is obtained. Our solution is illustrated using an example involving orthotropic materials.